Changes in serum levels of purines in an experimental infection by Leptospira interrogans serovar Icterohaemorrhagiae - Tonin A.A. (2015)
© 2014, Springer-Verlag London.The aim of this study was to measure the levels of purines in serum of rats experimentally infected with Leptospira interrogans serovar Icterohaemorrhagiae. For this purpose, 24 adult male Wistar rats were divided into two groups: A, not infected (subgroups A1 and A2), and B, infected (subgroups B1 and B2), which were intraperitoneally inoculated (day 0) with 2 × 108 leptospires/animal. Blood samples were collected on days 15 (A1 and B1) and 30 PI (A2 and B2) for analysis of purine levels in serum (adenosine triphosphate (ATP), adenosine diphosphate (ADP), adenosine monophosphate (AMP), adenosine, inosine, hypoxanthine, xanthine, and uric acid). The levels of ATP, AMP, adenosine, and xanthine increased (P < 0.015), while a reduction (P < 0.015) in the concentration of ADP and inosine occurred at day 15 PI. On day 30 PI, ATP, ADP, adenosine, and uric acid significantly increased (P < 0.015), while xanthine level was reduced (P < 0.015). The correlation among the infection and purine levels lead us to suggest the purinergic system as a compensatory mechanism during the leptospirosis infection, mainly due to the actions of ATP, which usually is involved in a pro-inflammatory response, followed by a protective action of ADP and adenosine on the clotting events, along with a protective cellular damage caused by the infection.